2017
DOI: 10.51406/jagse.v17i1.1790
|View full text |Cite
|
Sign up to set email alerts
|

COMPOSTED MUNICIPAL WASTE AS A SUBSTITUTE TO FURADAN IN THE MANAGEMENT OF Meloidogyne incognita INFECTION ON COWPEA

Abstract: There is a worldwide search for alternatives to synthetic pesticides in management of Root-knot nematodes (Meloidogyne incognita Kofoid and White 1919, Chitwood, 1949).  Screen-house studies were conducted to compare effects of composted municipal waste (CMW) and furadan on Root-knot nematode infection on cowpea (Vigna unguiculata L. Walp), var. Ife brown.  Treatment significantly reduced the number of M. incognita in the soil with furadan being the most effective followed by CMW. Growth and yield of cowpea wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Treatment T4 had the highest leaf area (401.36 cm 2 ), whereas T1 exhibited the minimum leaf area (293.85 cm 2 ). The result is under Odeyemi et al (2014), who observed that the plants treated with Tithonia leaf powder were a significantly higher in leaf area than the other cowpea plants. This study also noted that all plants grown in Tithonia leaf powder showed a higher leaf area than the control treatment.…”
Section: Leaf Areamentioning
confidence: 93%
See 2 more Smart Citations
“…Treatment T4 had the highest leaf area (401.36 cm 2 ), whereas T1 exhibited the minimum leaf area (293.85 cm 2 ). The result is under Odeyemi et al (2014), who observed that the plants treated with Tithonia leaf powder were a significantly higher in leaf area than the other cowpea plants. This study also noted that all plants grown in Tithonia leaf powder showed a higher leaf area than the control treatment.…”
Section: Leaf Areamentioning
confidence: 93%
“…Tithonia consists of various chemical compounds, including alkaloids, saponins, phenols and other substances (Taiwo and Makinde, 2005), accelerating plant growth and development (Nguemezi and Dzukam, 2016). Odeyemi et al (2014) also reported that cowpea plants in Tithonia added soil were taller than the other plants due to their ability to improve the soil properties. In the present study, the plant treated with powdered Tithonia had a high value in plant height compared to the control.…”
Section: Plant Height and Number Of Leavesmentioning
confidence: 97%
See 1 more Smart Citation